Intracerebral hemorrhage after mechanical thrombectomy in patient with acute anterior system strokes: Risk factors and effect on prognosis - Tatlı, Sinan; Aytac, Emrah; Balgetir, Ferhat; Genç, Şule Kavak (My University, 2024)
INTRODUCTION: Since 2015, endovascular therapy(ET) has become the standard treatment for patients with large vessel occlusion (LVO) in acute ischemic stroke (AIS). Recent studies have demonstrated the efficacy and safety of ET in selected patients such as onset time beyond six hours or with large infarct. However, the development of intracerebral hemorrhage (ICH) after mechanical thrombectomy (MT) represents one of the most significant complications. There is a currently insufficient data set on the risk factors associated with ICH after MT and its clinical significance. The aim of this study was to determine the significance and risk factors of ICH after ET for AIS. METHODS: A comprehensive review of patients who underwent MT at Fırat University Faculty of Medicine Stroke Center between 2021 and 2023 was performed. This review retrospectively scanned the files of these patients. The following variables were analysed: Admission NIHSS scores, ASPECT score, collateral status and whether intravenous thrombolysis (IV tPA) was administered. The time from the onset of symptoms to angiography, duration of MT, technique, number of thrombectomies, thrombectomy recanalisation rate, comorbidities, classification of hemorrhages and 3rd month mRS (Modified Rankin Scale) were analyzed retrospectively. RESULTS: The results of the study indicated that 80 patients (65.6%) did not experience any ICH, while 42 patients (34.4%) did experience ICH in the 24 hour control brain computer tomography (CT.) Of the patients, 18 (14.75%) developed hemorrhagic infarct (HI); 18 (14.75%) parenchymal hematoma (PH); 6 (4.9%) subarachnoid hemorrhage(SAH) and no patient developed symptomatic intracranial hemorrhage(sICH). In the analyses, time interval from symptom onset to artery puncture, hypertension (HT) and diabetes mellitus (DM) were found to be statistically significant risk predictors. DISCUSSION AND CONCLUSION: In our investigation, 68% of patients with HI exhibited a modified Rankin Scale (mRS) value greater than or equal to 3 at the three-month follow-up.Indicating that HI may not be a benign imaging finding. In patients who underwent bridging therapy with IV tPA and previously used antiplatelet and/or anticoagulant agents did not predispose to ICH significantly. A longer duration from symptom onset to puncture, HT and DM was found to increase the occurrence of ICH. Hemorrhage following ET was associated with a poor clinical outcome.
Keywords: Stroke; intracerebral hemorrhage; prognosis; mechanical thrombectomy